Characterisation of ground tyre rubber by using combination of FT-IR numerical parameter and DTG analysis to determine the composition of ternary rubber blend. (May 2017) - Datta, Sanjoy; Antos, Jan; Stocek, Radek
Abstract: Three different batches of ground tyre rubber (GTR), obtained from end of life (EOL) tyres, in the form of powder, were subjected to quantitative analysis using simple non-pyrolytic Fourier Transform Infrared (FT-IR) spectroscopy and derivative thermogravimetric (DTG) analysis. Two batches were based on EOL truck tyres varying in particle size, and one batch was based on EOL passenger car tyres. The focus was to derive a general method for finding multiple polymer blend compositions in different types of GTR for future efficient recycling applications of EOL tyres. The secondary aim was to evaluate the validity of the methodology independent of particle size. IR studies detected the presence of NR, SBR and BR characterized by peaks at 1375, 699 and 738 cm −1, respectively, in all the batches. Each of the blends was ternary, in which the ratio of two rubbers was exactly calculated by combined use of an existing infrared blend parameter ( P IR ) and the absorbance ratio of the characteristic peaks of the two rubbers in a baseline corrected IR spectrum. Then, using this calculated ratio on the results obtained from DTG, all three rubbers were quantified.